A fully automated nanoelectrospray tandem mass spectrometric method for analysis of Caco-2 samples - Van Pelt, Colleen K.; Zhang, Sheng; Fung, Eliza; Chu, Inhou; Liu, Tongtong; Li, Cheng; Korfmacher, Walter A.; Henion, Jack (Rapid communications in mass spectrometry, 2003)
Caco‐2 cells offer a means to rapidly screen permeability of drug candidates, allowing pharmaceutical companies to eliminate candidates unable to cross the intestinal barrier early in the discovery process. This screening process is typically performed by conventional liquid chromatography/tandem mass spectrometry (LC/MS/MS), which can require time‐consuming method development. An alternative to LC/MS/MS, automated nanoelectrospray tandem mass spectrometry (nanoESI‐MS/MS), is introduced. This novel approach requires an off‐line ZipTip™ desalting step followed by automated nanoESI‐MS/MS, using the NanoMate™ 100 and ESI Chip™. In addition to reduced method development time, automated nanoESI‐MS/MS also offers no carry‐over between samples, low sample consumption, and ease‐of‐use as compared with conventional pulled‐capillary nanoelectrospray. Furthermore, the infusion system described has the potential to be high‐throughput. A comparison of Caco‐2 samples analyzed both by LC/MS/MS and by automated nanoESI‐MS/MS is presented. The permeability and recovery data of the two compounds analyzed in this study obtained from conventional LC/MS/MS and by automated nanoESI‐MS/MS were in excellent agreement. Copyright © 2003 John Wiley & Sons, Ltd.